2023
DOI: 10.36897/jme/161717
|View full text |Cite
|
Sign up to set email alerts
|

Towards Metrology 4.0 in Dimensional Measurements

Abstract: The paper presents the transformations taking place in length and angle metrology related to Metrology 4.0, a measurement strategy resulting from Industry 4.0. Metrology in an industrial conditions is gradually focusing more and more on advanced measurement systems. The coming reality will see the development of communication between systems and their components, as well as the individual sensors belonging to them. The Internet of Things and artificial intelligence as well as the possibility of using augmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The field of metrology has witnessed significant advancements in measurement techniques and technologies over the years, driven by the demand for higher precision, efficiency, and automation in manufacturing processes. Traditional mechanical metrology techniques, such as vernier calipers, micrometers, and height gauges, formed the foundation of dimensional measurement (Sydenham, 1969;Wieczorowski, and Trojanowska, 2023). While still widely used for certain applications, these techniques have been largely supplanted by more advanced methods offering higher accuracy and automation (Lewis, 2021;Fabian et al, 2023).…”
Section: Fundamentals Of Precision Metrologymentioning
confidence: 99%
“…The field of metrology has witnessed significant advancements in measurement techniques and technologies over the years, driven by the demand for higher precision, efficiency, and automation in manufacturing processes. Traditional mechanical metrology techniques, such as vernier calipers, micrometers, and height gauges, formed the foundation of dimensional measurement (Sydenham, 1969;Wieczorowski, and Trojanowska, 2023). While still widely used for certain applications, these techniques have been largely supplanted by more advanced methods offering higher accuracy and automation (Lewis, 2021;Fabian et al, 2023).…”
Section: Fundamentals Of Precision Metrologymentioning
confidence: 99%
“…Platforms have been developed in this field to assist in design, such as PDSIDES (Platform for Decision Support in the Design of Engineered Systems), which is designed to facilitate end-to-end digital integration, customization, agile collaboration networks, open innovation, co-creation, crowdsourcing and product servitization. On the other hand, Metrology, which has associated the tools of the Fourth Industrial Revolution with its applications and development, is known as Metrology 4.0 [84]. It is projected that Metrology 4.0 will revolutionize calibration processes by reducing times and costs and processing measurement information in real time [85].…”
Section: Mechanical Engineering and Specialized Technical Fieldsmentioning
confidence: 99%
“…During the study, it was observed that the discussed issue not only aligns with Industry 4.0 concepts and its metrological counterpart, Metrology 4.0 [20,21], but also contributes to the sustainable development of CNC manufacturing. This aspect has been extremely significant in recent years, particularly for manufacturing companies, as this sector is responsible for 40% of global energy consumption and 25% of resource consumption [22].…”
Section: Introductionmentioning
confidence: 98%